Images of the Great Within: Cartographic Choices in Ming China. (2nd January 2018) - Hammond, Kenneth J.
Abstract : This paper uses three maps of Beijing from the sixteenth century to explore the range and variation of interests and agendas involved in the production of cartographic images of urban space in early modern China. One is a map from an official gazetteer, the second accompanied a privately produced guidebook/description of the city, and the third is a single broadsheet with a mix of cartographic and pictorial imagery aimed at a more popular audience. The treatment of the Imperial City and the Imperial Palace, known as the Great Within, is different in each map, from near complete obscurity to a rich and fantastic image of the emperor at work in his study. These maps illuminate the diversity of production in a period of rapid development in print publication and circulation.